The MBA handbook : - Cameron, Sheila (Pitman, 1991)
Appropriate for MBA and other Business Master's students, before they start their studies, to help them select the right MBA course. For all students on MBA and other Business Master's courses, to identify the skills they require throughout their course of study. The book is unique in its focus on the MBA market and the skills needed to undertake an MBA. Comprehensive and practical, it follows the successful three part organisation of previous editions. Part 1 provides guidance on choosing an MBA course and all the factors that should be considered. Part 2 covers pre-course preparation, such as getting organisational support. Part 3 deals with the requisite skills necessary for students to make the most of their course and to perform well in assessments.